Cytomegalovirus-specific lymphocyte transformations in subjects of different ages with primary immunodeficiency. - Tamura, T (1980)
The role of specific cell-mediated immune responses in human cytomegalovirus (CMV) infections was studied by an in vitro lymphocyte transformation test, using a whole blood culture. CMV-induced in vitro lymphocyte proliferation was mainly dependent on the presence of sensitized T-cells. Three of five seronegative patients with B-cell deficiency showed positive lymphocyte responses to CMV antigen. In contrast, a patient with ataxia-telangiectasia who was shedding the virus in urine did not show a cellular response to either CMV or phytohemagglutinin. Age-related differences were found in the CMV lymphocyte transformation test. The responses were generally low (P less than 0.025) in infants and higher in older children and adults. CMV lymphocyte transformation responses were lower in 15 children who were excreting CMV in urine when tested than in 17 seropositive children who were not excreting the virus.